Cannabis Growers in the United States: Findings From a National Household Survey 2010−2014. (July 2021) - Azofeifa, Alejandro; Pacula, Rosalie L.; Mattson, Margaret E.
Given the rapidly changing U.S. cannabis legislation landscape, the aim of this article is to describe individuals who self-reported growing cannabis in the past year by selected characteristics and geographical location. Using data from 2010 to 2014 National Survey on Drug Use and Health, we conducted bivariate chi-square tests and ran a multivariable logistic regression model to examine the indicators associated with growing cannabis. Approximately, 484, 000 individuals aged 12+ self-reported growing cannabis in the past year (1.6% of marijuana users). Predictors of growing cannabis included being male and self-reported reporting using cannabis for a greater number of days. Data showed differences in the proportion of cannabis growers by the state of residence. Obtaining a baseline estimate of cannabis growing practices prior to recreational cannabis markets emerging (2014) is important because such practices may undermine efforts to discourage diversion to youth. Tracking these acquisition patterns will better inform content for public health messaging and prevention education, particularly those targeting youth.